A new Permian–Triassic boundary brachiopod fauna from the Xinmin section, southwestern Guizhou, south China and its extinction patterns. Issue 3 (3rd July 2018) - Wu, Huiting; He, Weihong; Shi, G.R.; Zhang, Kexin; Yang, Tinglu; Zhang, Yang; Xiao, Yifan; Chen, Bing; Wu, Shunbao
Abstract : Wu, H.T., He, W.H., Shi, G.R., Zhang, K.X., Yang, T.L., Zhang, Y., Xiao, Y.F., Chen, B. & Wu, S.B., XX.XXXX.2018. A new Permian–Triassic boundary brachiopod fauna from the Xinmin section, southwestern Guizhou, south China and its extinction patterns. Alcheringa 00, 000–000. ISSN 0311-5518. A new brachiopod fauna comprising 31 species in 19 genera is described from a Permian–Triassic boundary section in Xinmin, Guizhou Province, Southwestern China. The brachiopods were collected from the Changhsingian (latest Permian) Changxing (=Changhsing) and Dalong (=Talung) formations and the lower Griesbachian (earliest Triassic) Daye Formation, which were deposited, respectively, in a shallow-water carbonate platform, upper offshore and carbonate platform settings. Among the brachiopods described and illustrated, a new species Juxathyris subcircularis is proposed. In addition, some species Araxathyris previously reported in south China have been discussed in detail and revised, with new morphological information. In particular, internal structures are provided for the first time for Orthothetina and Araxathyris species reported from south China. In addition, important clarifications are also provided on the morphology and diagnoses for Haydenoides, Martinia, Crurithyris and Transcaucasathyris, as well as for Paryphella transversa . Huiting Wu School of Earth Sciences, China University of Geosciences, Wuhan 430074, PR China and School of Life and Environmental Sciences, Deakin University, Melbourne Burwood Campus, 221 Burwood Highway, Burwood, Victoria 3125, Australia ; Weihong He [ whzhang@cug . edu . cn ] State Key Laboratory of Biogeology and Environmental Geology, School of Earth Sciences, China University of Geosciences, Wuhan 430074, PR China ; G . R . Shi [ guang . shi@deakin . edu . au ] School of Life and Environmental Sciences, Deakin University, Melbourne Burwood Campus, 221 Burwood Highway, Burwood, Victoria 3125, Australia ; Kexin Zhang State Key Laboratory of Biogeology and Environmental Geology, School of Earth Sciences, China University of Geosciences, Wuhan 430074, PR China ; Tinglu Yang Faculty of Geosciences, East China University of Technology, Nanchang 330013, PR China ; Yang Zhang School of Earth Sciences and Resource, China University of Geosciences, Beijing 100083, PR China ; Yifan Xiao and Bing Chen School of Earth Sciences, China University of Geosciences, Wuhan 430074, PR China ; Shunbao Wu, School of Earth Sciences, China University of Geosciences, Wuhan 430074, PR China .